Not Your Everyday Duodenal Ulcer: Massive Gastrointestinal Bleed Secondary to Extramedullary Plasma Cell Myeloma. Issue 4 (20th April 2023) - Fiske, Hannah; Dougherty, Brian; Ward, Christopher; Claus, Jessica; Dannheim, Katelyn; Chen, Sonja; Ferreira, Jason
ABSTRACT: The differential for gastrointestinal (GI) bleeding is broad, ranging from peptic ulcers and Helicobacter pylori infection to variceal hemorrhage and neoplasms. The rarer causes of GI bleeds are frequently overlooked and as such can ultimately be more dangerous. Extramedullary multiple myeloma, an atypical plasma cell dyscrasia arising outside of the bone marrow, involves the GI tract in <5% of cases and often presents with nonspecific symptoms. We describe a rare case of such GI involvement of a plasma cell tumor, with subsequent transmural duodenal ulceration involving the gastroduodenal artery, ultimately resulting in a fatal GI bleed.